2017
DOI: 10.1111/papr.12615
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on the Influence of Intraoperative Remifentanil versus Fentanyl on Acute and Chronic Pain after Cardiac Surgery

Abstract: Intraoperative use of remifentanil during cardiac surgery does not impact chronic postoperative pain 1 year after surgery. Nevertheless, remifentanil increases analgesic requirements and thoracic pain until 3 months after surgery, and its use is therefore less favorable during cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…A large study using the PAIN OUT database (see http://pain-out.med.unijena.de/) found an association between worse pain-related outcomes and intraoperative use of remifentanil (63). More recent studies have strengthened this finding, with younger patients seeming to be at higher risk (64). The cause of the apparent higher risk of OIH with remifentanil compared to other opioids is unclear, but may be related to the fast onset/ offset of its action.…”
Section: Clinical Evidence For Oihmentioning
confidence: 99%
“…A large study using the PAIN OUT database (see http://pain-out.med.unijena.de/) found an association between worse pain-related outcomes and intraoperative use of remifentanil (63). More recent studies have strengthened this finding, with younger patients seeming to be at higher risk (64). The cause of the apparent higher risk of OIH with remifentanil compared to other opioids is unclear, but may be related to the fast onset/ offset of its action.…”
Section: Clinical Evidence For Oihmentioning
confidence: 99%
“…Interestingly, this effect was more pronounced in younger patients and in those receiving a higher dose of remifentanil. 18 Another observational study showed worse patient-reported outcomes (higher “worst pain” and lower satisfaction with pain control) after thyroidectomy when they received remifentanil as compared with patients receiving fentanyl as intraoperative opioid. 19 Such and other studies highlight the importance of adopting strategies to decrease the risk of remifentanil-induced hyperalgesia (RIH), from the avoidance of high doses of remifentanil to the implementation of drugs specifically targeting the mechanisms of OIH/RIH.…”
Section: Introductionmentioning
confidence: 99%
“…Besides standard postoperative analgesics, the use of corticosteroids, N-methyl-D-aspartate (NMDA) antagonists, alpha-2 agonists, local anesthetics and gabapentinoids are all suggested to reduce the risk for CPSP after cardiac surgery [5]. However, no specific therapy is verified to protect against CPSP [10][11][12].…”
Section: Introductionmentioning
confidence: 99%